Conserved features of TERT promoter duplications reveal an activation mechanism that mimics hotspot mutations in cancer - Barger, Carter J.; Suwala, Abigail Kora; Soczek, Katarzyna M.; Wang, Albert S.; Kim, Min Y.; Hong, Chibo; Doudna, Jennifer A.; Chang, Susan M.; Phillips, Joanna J.; Solomon, David; Costello, Joseph F. (Nature Communications, 2022)
Mutations in the TERT promoter represent the genetic underpinnings of tumor cell immortality. Beyond the two most common point mutations, which selectively recruit the ETS factor GABP to activate TERT, the significance of other variants is unknown. In seven cancer types, we identify duplications of wildtype sequence within the core promoter region of TERT that have strikingly similar features including an ETS motif, the duplication length and insertion site. The duplications recruit a GABP tetramer by virtue of the native ETS motif and its precisely spaced duplicated counterpart, activate the promoter and are clonal in a TERT expressing multifocal glioblastoma. We conclude that recurrent TERT promoter duplications are functionally and mechanistically equivalent to the hotspot mutations that confer tumor cell immortality. The shared mechanism of these divergent somatic genetic alterations suggests a strong selective pressure for recruitment of the GABP tetramer to activate TERT.